Peran World Central Kitchen (WCK) Dalam Menangani Krisis Kelaparan di Gaza Akibat Invasi Militer Israel (2023-2024) - Davelly, Salsabilla Putri; Alfajri; Sundari, Rio (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
The military invasion by Israel against Gaza, which began on October 7, 2023, has worsened the hunger crisis. This research aims to determine the role of World Central Kitchen (WCK) in addressing the hunger crisis in Gaza in 2023- 2024. This research uses Clive Archer's theory of international organisation roles to examine WCK's role in addressing the hunger crisis in Gaza. The methodology used in this research is a descriptive qualitative approach with secondary data sources obtained from journals, books, reports, and media news. The research results indicate that WCK has significantly fulfilled its roles as an instrument, arena, and independent actor. The WCK's first role is an instrument for humanitarian food aid programs by building community kitchens and collaborating with the governments of other countries and local organisations to distribute food. The second role is an arena, which means making the WCK organisation a workplace for workers and volunteers from all over the world. Then, the third role is as an independent actor, namely WCK is an independent organisation in terms of funding and also receives donations from other institutions without any binding interests except humanitarian ones. In addition to these roles, WCK also faces challenges, including difficulties in obtaining assistance and potential threats to the safety of its workers during humanitarian operations. Keywords: Role, World Central Kitchen, Hunger, Gaza, Israel, Invasion, International Organisation